Telework: A Systematic Literature Review (SLR) - Bahariawansyah, Ahmad Sidqi; Nadia, Fiona Niska Dinda (Fakultas Ekonomi Universitas Kadiri, 2024)
The application of the telework work system in this era has been applied to all lines of the Company's field. The purpose of this systematic review literature review is to analyze how the implementation of the Telework work system using the Preferred Reporting Items for Systematic Review method. Data was obtained from the online database, namely Scopus with a range of 2021 to 2023 and 53 articles were obtained. By using keyword searches, namely